PENDEKATAN SOSIO-EMOSIONAL DALAM MANAJEMEN KELAS PADA PEMBELAJARAN DI SEKOLAH - Ceren Desta Joina; M. Irfansyah Afsalu Ramedhon; Dyah Kusumaningtyas; Nurlaila Ana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The socio-emotional approach is a learning approach that emphasizes the development of students' social and emotional competencies in addition to academic achievement. This approach is important because students not only need to master knowledge but also need the ability to manage emotions, build positive social relationships, and adapt to the learning environment. This study aims to describe the implementation of the socio-emotional approach in learning and its impact on student development. The research employed a library research method by reviewing various scientific articles, journals, and other relevant literature related to the socio-emotional approach in education. The findings indicate that the implementation of the socio-emotional approach can be carried out through fostering positive relationships between teachers and students, creating a conducive and comfortable classroom climate, and providing social and emotional support through communication, positive reinforcement, and collaborative activities. Furthermore, this approach contributes various positive outcomes in the learning process, such as improving students’ motivation and academic achievement, strengthening social interactions, enhancing emotional regulation and conflict resolution skills, fostering empathy and positive character traits, promoting emotional well-being, and creating a safe and supportive learning environment. Therefore, the socio-emotional approach can serve as an alternative learning approach that supports students’ balanced academic, social, and emotional development.